2020
DOI: 10.3390/microorganisms8060827
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Potential of a Multidrug-Resistant Escherichia coli Strain Belonging to the Emerging Clonal Group ST101-B1 Isolated from Bloodstream Infection

Abstract: Escherichia coli EC121 is a multidrug-resistant (MDR) strain isolated from a bloodstream infection of an inpatient with persistent gastroenteritis and T-zone lymphoma that died due to septic shock. Despite causing an extraintestinal infection, previous studies showed that it did not have the usual characteristics of an extraintestinal pathogenic E. coli. Instead, it belonged to phylogenetic group B1 and harbored few known virulence genes. To evaluate the pathogenic potential of strain EC121, an extensive genom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 121 publications
1
12
0
Order By: Relevance
“…Our results demonstrated that E. coli was present at a rate of 5.02% in nasal samples, 19.8% in fecal samples, and 37% in milk samples, as shown In this work, the lowest positivity rates for E. coli were 3.8%, 5%, 5.2%, and 6.4% from nasal swabs of sheep, buffaloes, cattle, and goats, respectively (Table -3). This finding is in agreement with the previous studies [32,33] that found that E. coli was present at a low rate of 4.22% in healthy and diseased animals with respiratory signs. In addition, it was reported [34] that the rate of bacteria in the bovine nasopharyngeal tract was very low compared with the rates at other anatomical sites [35].…”
Section: Discussionsupporting
confidence: 94%
“…Our results demonstrated that E. coli was present at a rate of 5.02% in nasal samples, 19.8% in fecal samples, and 37% in milk samples, as shown In this work, the lowest positivity rates for E. coli were 3.8%, 5%, 5.2%, and 6.4% from nasal swabs of sheep, buffaloes, cattle, and goats, respectively (Table -3). This finding is in agreement with the previous studies [32,33] that found that E. coli was present at a low rate of 4.22% in healthy and diseased animals with respiratory signs. In addition, it was reported [34] that the rate of bacteria in the bovine nasopharyngeal tract was very low compared with the rates at other anatomical sites [35].…”
Section: Discussionsupporting
confidence: 94%
“…The ST101, a major ST in CC101, has been reported worldwide, although not yet regarded as a member of the pandemic clones. ESBL/AmpC-EC clone type ST101 has attracted renewed global attention in human ESBL/AmpC-producing ExPEC infections given its enhanced virulence and pan-drug resistance ( Yoo et al, 2013 ; Manges et al, 2019 ; Santos et al, 2020 ), and has been reported to cause hemolytic uremic syndrome ( Mellmann et al, 2008 ) and bloodstream infections ( Santos et al, 2020 ). Consistently, in the clonal population structure analysis based on the ExPEC VF profiles and phylogenetic groups using the program STRUCTURE, we also identified a highly virulent profile of ESBL/AmpC-EC ST101 clone.…”
Section: Discussionmentioning
confidence: 99%
“…The spread of ESBL/AmpC-EC or CP-EC is of great concern because it could aid the emergence and spread of pathogens that are difficult to treat even with an antimicrobial agent of choice regarded as a final treatment option ( Nathisuwan et al, 2001 ; Cortes et al, 2010 ). In addition, as ESBL/AmpC- or CP-producing extra-intestinal pathogenic E. coli (ExPEC) clones are increasingly reported worldwide, the virulence potential of ESBL/AmpC-EC or CP-EC has also become an issue ( Schaufler et al, 2016 ; Day et al, 2019 ; Santos et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Together these methodologies enable the screening of the ExPEC strains that either harbor intrinsic virulence or uropathogenic potential, in diverse sources, like water, food, and gut, favoring the identification of their reservoirs. However, these criteria fail to classify all strains isolated from extraintestinal infections (Spurbeck et al, 2012 ; Santos et al, 2013 , 2020b ; Freire et al, 2020 ) and some clinical lineages with epidemiological importance also do not meet these criteria (Bert et al, 2010 ; Olesen et al, 2012 ; Manges and Johnson, 2015 ; Manges et al, 2017 , 2019 ; Campos et al, 2018 ; Yamaji et al, 2018 ; Santos et al, 2020a , b ).…”
Section: Introductionmentioning
confidence: 99%